Tumor necrosis factor alpha—an underestimated risk predictor in patients undergoing transcatheter aortic valve replacement (TAVR)?. Issue 11 (25th September 2021) - Mirna, Moritz; Holnthoner, Mario; Topf, Albert; Jirak, Peter; Fejzic, Dzeneta; Paar, Vera; Kellermair, Jörg; Blessberger, Hermann; Reiter, Christian; Kammler, Jürgen; Motloch, Lukas J.; Jung, Christian; et al.
Abstract: Background: Systemic inflammation has been identified as a major cardiovascular risk factor in patients undergoing transcatheter aortic valve replacement (TAVR), yet currently, it is not adequately portrayed in scores for pre‐interventional risk assessment. The aim of this study was to investigate the predictive ability of TNF‐α in TAVR. Methods: A total of 431 patients undergoing transfemoral TAVR were enrolled in this study. Blood samples were drawn prior to intervention, 24 h post‐intervention, 4, 5, and 7 days post‐intervention, and 1, 3, and 6 months post‐TAVR. Results: In a univariate Cox proportional hazard analysis, plasma concentrations of TNF‐α after 24 h and after 5 days were associated with mortality after 12 months (after 24 h: HR 1.002 (1.000–1.004), p = 0.028; after 5d: HR 1.003 (1.001–1.005), p = 0.013). This association remained significant even after correction for confounders in a multivariate Cox regression analysis. Additionally, cut‐offs were calculated. Patients above the cut‐off for TNF‐α after 5d had a significantly worse 12‐month mortality than patients below the cut‐off (18.8% vs. 2.8%, p = 0.046). Conclusion: Plasma levels of TNF‐α after 24 h and 5 days were independently associated with 12‐month mortality in patients undergoing TAVR. Thus, TNF‐α could represent a novel biomarker for enhanced risk stratification in these patients. Abstract : A total of 431 patients undergoing transfemoral TAVR were enrolled in this study. In Cox proportional hazards analysis, plasma concentrations of TNF‐α after 24 h and after 5 days were independently associated with mortality after 12 months, which remained significant even after correction for confounders in a multivariate analysis. Thus, TNF‐α could represent a novel biomarker for enhanced risk stratification in these patients.